PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE PAIRED STORYTELLING UNTUK MENINGKATKAN HASIL BELAJAR IPS: Penelitian Tindakan Kelas Pada Siswa Kelas VIII-3 di SMP Negeri 28 Tangerang - Abdull, Meyga Fernanda; Siswono, Eko; Saipiatuddin (Edukasi IPS, 2020)
This research is airned at potraying the improvement of students learning outcome and activeness in social science subject using Cooperative Tipe Paired Storytelling model instruction. The research method used in this study was Classroom Action Research conducted collaboratively with social studies teacher. This research is conducted in VIII-3 Public Middle School 28 Tangerang with the total participants is 35 students. This research uses three cycles, in which each cycle consists of four stages, namely: Planning, Acting, Observation, and Reflection. The findings of this research showed that there is an improvement of students learning outcome and activeness in social science subject. In cycle I, 37% or 13 students scored above KKM 72. In cycle II, 60% or 21 students scored above KKM 72. In cycle III, 89% or 31 students scored above KKM 72. The percentage of the improvement of students skill in asking questions, answering, giving opinions, and solve the problem. In conclusion, the implementation of Cooperative Tipe Paired Storytelling model instruction can improve the students learning outcome and activeness, especially in VIII-3 Public Middle School 28 Tangerang. Therefore, the implementation of Cooperative Tipe Paired Storytelling model instruction is recommended to be used by all of the social science teachers in creating the enjoyable learning atmosphere and improving the students learning outcome and activeness.